Gastronomia, culinária e mídia: estudo dos ambientes midiáticos e das linguagens da comida e da cozinha - Jacob, Helena Maria Afonso (2013)
Under the guidance of Professor PhD Lucrecia D Alessio Ferrara, this research entitled Gastronomy, Cuisine and Media - a study of food and cooking media environments and languages investigates the gastronomy and cuisine language construction in food and cooking media environments, and its importance in contemporary media universe. It is considered that in this scenario the culture system composed by the media is reframed by the gastronomy culture system and vice versa, creating a new meaning web for both. Both the gastronomy and the cuisine form languages of qualified meaning spaces - so spatialities - which are important to a contemporary media analysis. In the last 10 years, it is possible to notice in mass media communication the intense use of cuisine and especially gastronomy themes in magazines, newspapers, television shows and internet sites, making such a system to be processed as a media capable of shaping social, economic and cultural preferences, tastes and palates. This research concerns on how media - both print (newspapers and magazines), television and digital ones - build these media environments and how such communication strategy affects the symbolic relationship between the people and the food. The theoretical framework was constituted primarily by Semiotics of Culture of Yuri Lotman, and the work of Lucrécia Ferrara and Muniz Sodré. Throughout the analysis of the research corpus, which is consisted of language construction and communication strategies examples towards cuisine and gastronomy in the media, the research was conducted in order to consolidate the main hypothesis: we believe that nowadays gastronomy has become an independent media, such is the communication and cultural relevance of its performance